Construction of Health Care Indicators for Elderly Males Based on Phase Angle - Takeyama, Yuki; Fujii, Katsunori (European Journal of Applied Sciences, 2022)
In Japan, preventing the need for care is central to the aim of extending healthy life expectancy in elderly people, and many days care service and other facilities have been built. However, health indicators for people at the time they move into residential care facilities have not been established. In a previous study, we surveyed phase angle in general elderly women and evaluated the phase angle of those who require care by constructing a reference chart for its evaluation. From the results, it was shown that the range of −1.0 SD the level of general elderly women was a standard for care need level. However, since there are obviously sex differences between men and women in phase angle, constructing separate evaluation indicators for men and women is an urgent task. In this study, we analyzed the changes in phase angle with age in general elderly men, and constructed a span evaluation chart based on those changes with age. The phase angle of men who require care was applied to the constructed span evaluation chart, and standards for care need level were sought. The results showed a trend for the phase angle in people who require care to be distributed at below 5.5° for the whole body and 4.0° for the legs. Thus, the phase angle of people who require care was revealed to be distributed in the range of −1.0 ± 1.0 SD that of general elderly men. Using the phase angle aging span evaluation chart, a standard for care need level was presented and its validity as a health care indicator in the elderly is thought to have been shown.